MODERN MANAGEMENT PRACTICES AND FIRMâS PERFORMANCE - Ellitan, Lena (Proceeding SENDI_U, 2015)
To date, the role of technology as factors of success in competitive arena has become a subjectof significant interest amongst practitioners and academicians. This paper is based on a fieldinvestigation via mailed questionnaire that was sent to CEOs (Chief Executive Officer) ofmanufacturing firms Indonesia that involved small and medium companies (SMEs). Thisresearch is an exploratory one that was conducted to invetigate the extent of soft technologyadoption and to examine the relationship between the level of soft technological adoption onfirm performance, in term of financial and manufacturing performance. The significantrelationship was found between the level of soft technological adoption (TQM, MRP2 andBenchmarking) and performance implies the fact that adoption of TQM, MRP2, andbenchmarking can improve the performance of an organization. TQM has an important role forimproving manufacturing performance, while MRP2 plays an important role for enhancingfinancial and manufacturing performance. Further, benchmarking is very importance to be donefor increasing financial performance. This study also indicates that Indonesian manufacturingSMEs that success in adopting TQM, MRP2 and Benchmarking can compete successfully. Inaddition, JIT and TPM seem to be left out by Indonesian manufacturing SMEs. The effect of JITand TPM on financial and manufacturing performance is not significant.